PENGARUH POTENSI CAGAR BUDAYA, PARIWISATA, DAN PARTISIPASI MASYARAKAT TERHADAP PENGEMBANGAN WILAYAH DI KECAMATAN BELAKANG PADANG - Raharjo, Teguh Eko; Sidabutar, Yuanita FD; Tanjung, Raflis; Raymond; Marzuki, Farid Ahmad (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to analyze the effect of potential cultural heritage, tourism, and community participation on regional development in Padang Rear District. This study uses a combination method between qualitative and quantitative which applies an approach with a sequential exploratory strategy. The results of the study formulated that at the study site there was a building area allegedly having the characteristics of cultural heritage but had not been determined as an object of cultural heritage through government policy so that there was no preservation made. The results also showed that in the development of regional planning depends on the potential of its cultural preservation as a tourist destination, the tourism component of cultural heritage (facilities in supporting tourism), as well as community participation (local and non-local) which also plays a role in the development of tourism so that the tourism area is realized. Sustainable culture until the future. Furthermore, researchers provide several recommendations to the results of this study so that the development of tourism cultural heritage in Padang Rear District can be realized.